Hydrogels: Pd‐Porphyrin‐Cross‐Linked Implantable Hydrogels with Oxygen‐Responsive Phosphorescence (Adv. Healthcare Mater. 6/2014). Issue 6 (June 2014) - Huang, Haoyuan; Song, Wentao; Chen, Guanying; Reynard, Justin M.; Ohulchanskyy, Tymish Y.; Prasad, Paras N.; Bright, Frank V.; Lovell, Jonathan F.
<x xml:space="preserve">Abstract</x> J. F. Lovell and team present a new strategy to create a biocompatible implantable hydrogel for non‐invasive oxygen sensing. On page 891, a tetracarboxy porphyrin is reacted with PEG diamines under conditions that result in nearly quantitative dye incorporation. Polyamide is formed with millimolar porphyrins exhibiting near infrared phosphorescence, ideal for in vivo detection. The spatially constraining mesh of the PEG‐porphyrin matrix prevents porphyrin aggregation that would normally occur at such dye concentrations and attenuate the phosphorescence. The hydrogel can be implanted in mice for weeks without signs of toxicity, signal loss or polymer degradation, and could non‐invasively detect changes in subcutaneous oxygen levels via transdermal phosphorescence detection. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>